Eudaimonism and the Ground of Normative Reasons - Jung, Kevin (Journal of religious ethics, 2022)
This essay develops an argument against eudaimonism in support of John Hare's earlier critique of eudaimonism. In contrast to Hare, who mounts a Kantian-Scotist objection to what he calls a single-source view of motivation in eudaimonism, my critique of eudaimonism focuses on the ground of normative reasons in eudaimonism while also taking a page from Scotus's ethics. I argue that the main issue with eudaimonism is with the ultimate end and manner of our willing, which fails to correspond to the right ordering of love based on the nature of goodness in the object.